Legal Certainty of the Electronically Integrated Business Licensing System: A Comparative Regulatory Analysis between Indonesia and Malaysia - Bachtiar, Ronald Reagan Jap; Sudirman, Lu; Disemadi, Hari Sutra (CV. Social Politic Genius (SIGn), 2026)
The electronic licensing transformation through the OSS system in Indonesia faces administrative dysfunction caused by the collision of institutional sectoralism and regional autonomy. This contradicts the governance efficiency of the MalaysiaBiz ecosystem in Malaysia, which operates more adaptively. This research aims to compare the electronic licensing regulatory framework in both countries and formulate a digital administrative governance reconstruction strategy in Indonesia. Employing a normative legal method with statute, comparative, historical, and conceptual approaches, this study examines primary legal materials comprising Law Number 6 of 2023 and the Companies Commission of Malaysia Act 2001. The research results indicate that Indonesia’s licensing architecture rests upon a rigid rule-based approach with ex-ante supervision. Conversely, Malaysia’s efficiency is based on a precise separation between centralized entity registration and local licensing authorities, supported by a strict ex-post compliance audit system. Addressing this gap, this research recommends the implementation of a hybrid regulatory approach for Indonesia’s licensing governance. In the upstream phase, reduce authority fragmentation and regional autonomy impediments by applying the deemed approval instrument. In the downstream phase, this policy must be counterbalanced by the establishment of a cross-authority sanction ecosystem between the OSS management and the Ministry of Law to execute the striking off the register sanction for spatial planning violating corporations. This hybrid approach, contingent on equalizing digital infrastructure, is expected to uphold the supremacy of the legal certainty principle while enhancing Indonesia’s investment competitiveness in the ASEAN economic integration era.